Constitutional Struggle and Indigenous Resistance in Latin America: The Case of Panama. (November 2014) - Fisher, Eloy
While inequality in Latin America has decreased, being poor and being of indigenous descent are still interchangeable. Uneven progress and policy dereliction with respect to indigenous groups have their consequences: increasingly organized indigenous movements in Latin America struggle today to reclaim and provide new spaces of citizenship around notions of local governance of natural resources and self-determination under harsh social realities. As globalization flattens production and consumption beyond the purview of the traditional nation-state, excluded groups like the indigenous peoples of Latin America have quickly assumed a position of political prominence. Indigenous movements fill the vacuum left by urban groups that today marginally participate in reaping the rewards of higher, commodity-driven growth. In Latin America, indigenous demands have turned into calls for constitutional reform against the interests of governments that wish to develop valuable mineral resources in indigenous regions. However, these indigenous movements are at a crossroads: while instrumental, their situation in political alliances is precarious as governments resort to capital-intensive strategies for the development of resources under their care. Si bien la desigualdad en América Latina ha disminuido, ser pobre y ser de ascendencia indígena aún son intercambiables. Progreso desigual y negligencia en el cumplimiento de políticas con respecto a los grupos indígenas tienen sus consecuencias: los movimientos indígenas cada vez más organizados de América Latina luchan hoy para reclamar y ofrecer nuevos espacios de la ciudadanía acerca de las nociones de gobernabilidad local de los recursos naturales y de la autodeterminación en virtud de las realidades sociales difíciles. Dado que la globalización aplana la producción y el consumo más allá del ámbito de competencia del Estado-nación tradicional, los grupos excluidos, como los pueblos indígenas de América Latina, han asumido rápidamente una posición de prominencia política. Los movimientos indígenas llenan el vacío dejado por los grupos urbanos que hoy participan marginalmente en recoger las recompensas del superior crecimiento del producto impulsado. En América Latina, las demandas indígenas se han convertido en reclamaciones para la reforma constitucional en contra de los intereses de los gobiernos que deseen desarrollar recursos minerales valiosos en las regiones indígenas. Sin embargo, estos movimientos indígenas se encuentran en una encrucijada: si bien instrumental, su situación en las alianzas políticas es precaria ya que los gobiernos recurren a estrategias de uso intensivo de capital para el desarrollo de los recursos bajo su cuidado.